Quality of Life Among Women at Menopause - Marni Marni; Siti Farida; Putri halimu Husna; Wahyuningsih Wahyuningsih; Domingos Soares; Kresna Agung Yudhianto (Jurnal Kesehatan Masyarakat, 2025)
This study aimed to examine factors related to the quality of life in women at menopause. This cross-sectional study included 53 women aged 45 to 65 who were at menopause, with self-reported good general health and not receiving hospital treatment, and were willing to participate as respondents. The Menopause-Specific Quality of Life (MENQOL) questionnaire assessed quality of life across four domains: vasomotor, psychosocial, physical, and sexual. Data analysis involved univariate analysis using frequency tables and crosstabs, bivariate analysis using correlation tests, and multivariate analysis using chi-square tests. The bivariate analysis revealed a significant association between education and quality of life (p = 0.000). Additionally, the age of menarche (p = 0.022) and income (p = 0.006) were significant factors. The multivariate analysis confirmed that both income (p = 0.021) and frequency of sexual activity (p = 0.032) significantly impacted the quality of life. The quality of life among women at menopause was influenced by factors such as education, age of menarche, income, and early menopause. Income and the frequency of sexual activity particularly affected the quality of life, specifically in the sexual domain. This research holds implications highlighting the need for targeted interventions to help women prepare for menopause and mitigate physical complaints.